2017
DOI: 10.5603/gp.a2017.0109
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcomes of pre-induction of labor with a 200 μg misoprostol vaginal insert

Abstract: Objectives: Labor induction is indicated in 20% to 40% of pregnancies. Over half of pregnancies qualified for the induction of labor require stimulation of the cervix to ripen. The drug used increasingly more often in pre-induction is the PGE-1 prostaglandin analog -misoprostol 200 μg. Material and methods:The study includes a total of 100 patients qualified for labor pre-induction with Misodel® (misoprostol 200 μg vaginal insert). The study group comprises two subgroups: primigravidas and multiparas. Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
2
1
1
Order By: Relevance
“…This prospective clinical observational study confirmed the efficacy of MVI (controlled and sustained-release misoprostol 7 µg/h for up to 24 h) in both nulliparous and parous women who all had medical reasons for induction of labor, such as being post-term (> 40 + 0 weeks of gestation) diabetes, or hypertension. In our study, the median time from administration of the MVI to vaginal delivery for women of any parity was 14.0 h. This is comparable with the lately published data of Mayer et al [ 18 ] and Jagielska et al [ 19 ], but lower than in the phase 3 EXPEDITE trial by Wing et al [ 7 ] who reported a median time to vaginal delivery of 21.5 h. Another study by Bolla et al [ 16 ] that included 200 women who received MVI had a mean time from start of induction to vaginal delivery of approximately 17 h and 45 min. In our study, the parous group had a median time to vaginal delivery of 11.9 h, which is comparable with data published by Mayer et al [ 18 ] and the EXPEDITE trial by Wing et al [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…This prospective clinical observational study confirmed the efficacy of MVI (controlled and sustained-release misoprostol 7 µg/h for up to 24 h) in both nulliparous and parous women who all had medical reasons for induction of labor, such as being post-term (> 40 + 0 weeks of gestation) diabetes, or hypertension. In our study, the median time from administration of the MVI to vaginal delivery for women of any parity was 14.0 h. This is comparable with the lately published data of Mayer et al [ 18 ] and Jagielska et al [ 19 ], but lower than in the phase 3 EXPEDITE trial by Wing et al [ 7 ] who reported a median time to vaginal delivery of 21.5 h. Another study by Bolla et al [ 16 ] that included 200 women who received MVI had a mean time from start of induction to vaginal delivery of approximately 17 h and 45 min. In our study, the parous group had a median time to vaginal delivery of 11.9 h, which is comparable with data published by Mayer et al [ 18 ] and the EXPEDITE trial by Wing et al [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…The median time from administration of vaginal misoprostol to vaginal delivery was 16 hours regardless of the parity status. This result is similar to what was found in a few recent published articles for example Mayer et al 22 and Jagielska et al 23 . About 62% of induced women received 2 or less doses of misoprostol and the bishop score was less or equal 4 in 66% of induced women, among whom the vaginal delivery rate was 75.8%, while 34% of induced women had bishop score of more than 4 (considering the of possibility of individual variability in the assessment of bishop score), the success rate for vaginal delivery in this group was 70.6%.…”
Section: Discussionsupporting
confidence: 93%
“…However, observational studies in the Polish population indicate a higher percentage of CS. In one of the works in the Polish cohort of patients published by Jagielska et al [13] the percentage of caesarean sections was 40.58% in the primagravida and 16.13% in the plurigravida group, and the overall percentage of caesarean sections in the group of patients induced by MVI was 33%, which is lower than in our cohort. However, in the study cited above [12], the proportion of plurigravidas to the primagravidas in the studied group (31/69 = 0.45) was higher, and in our studies it was lower (24/111 = 0.21), (p = 0.018).…”
Section: Discussioncontrasting
confidence: 77%